Intelligent trading/metering/billing systems ITMBS-III - Er, Jonathan Boon York (2010)
As Singapore is moving towards a Clean Energy environment, several implementation and research activities have been on going to make this possible. The Clean Energy industry comprises a broad range of areas, including solar power, fuel cells, wind power, energy efficiency and carbon trading. Singapore aims to grow this industry, generating S$1.7 billion of value‐added by 2015. This Intelligent/ Trading /Metering /Billing /System (ITMBS) will be the upgraded version of Automatic Metering/Reading/Billing System (AMRBS) developed by the earlier FYP groups. Previously the AMRBS is a system catered to accumulate readings automatically and bill the electricity consumption of each user, whereas ITMBS is an improvised version which allows the users to select the electricity suppliers to utilize meter electricity sold to the power grid by the users. This will facilitate the new requirement for electricity metering after considering family‘s renewable power (such as fuel cell, solar and wind) produced. The whole system consists of Mechanical Energy Meter (MEM), Bidirectional Digital Energy Meters (BDEM), Digital Water Meter (DWM), Digital Gas Meter (DGM), Power Line Communication Network (PLCN), and Computer Database and Billing Software (CDBS). The report covers an introduction to the implementation of Clean Energy in Singapore, a review on the system done by the previous group and the improvised DEM on both hardware and software done by the author.